2011
DOI: 10.1186/1556-276x-6-188
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of a confined slot impinging jet with nanofluids

Abstract: BackgroundHeat transfer enhancement technology concerns with the aim of developing more efficient systems to satisfy the increasing demands of many applications in the fields of automotive, aerospace, electronic and process industry. A solution for obtaining efficient cooling systems is represented by the use of confined or unconfined impinging jets. Moreover, the possibility of increasing the thermal performances of the working fluids can be taken into account, and the introduction of nanoparticles in a base … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(55 citation statements)
references
References 55 publications
2
48
0
Order By: Relevance
“…The nanofluid specific heat capacity is given by [51][52][53] (1 ) (25) The Bruggeman model [52,56], which considers interaction among spherical particles with various concentrations of inclusion, was used for modelling thermal conductivity of the nanofluid. The thermal conductivity obtained with the Bruggeman model compares very well with Maxwell's model of the classic effective medium theory which was shown to be accurate for well-dispersed particles in a benchmark study of thermal conductivities of nanofluids [57].…”
Section: Thermophysical Properties Of the Heat Transfer Fluidmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanofluid specific heat capacity is given by [51][52][53] (1 ) (25) The Bruggeman model [52,56], which considers interaction among spherical particles with various concentrations of inclusion, was used for modelling thermal conductivity of the nanofluid. The thermal conductivity obtained with the Bruggeman model compares very well with Maxwell's model of the classic effective medium theory which was shown to be accurate for well-dispersed particles in a benchmark study of thermal conductivities of nanofluids [57].…”
Section: Thermophysical Properties Of the Heat Transfer Fluidmentioning
confidence: 99%
“…Whereas, the specific heat capacity was determined from the commonly used expression that assumes thermal equilibrium between particles and the surrounding liquid [51,52].…”
Section: Thermophysical Properties Of the Heat Transfer Fluidmentioning
confidence: 99%
“…The investigation on nanofluid behaviour is becoming more and more popular, as testified by recent reviews and papers on this issue [35][36][37][38][39][40][41][42][43][44] but inconsistencies in published data and disagreements on the heat transfer mechanisms have been underlined by Keblinski et al [45] and recently by Gherasim et al [46]. However, a few examples of studies on nanofluids in impinging jets have been investigated experimentally and numerically and, according to the best knowledge of the present authors, their investigations have been reported in [46][47][48][49][50][51][52][53][54][55][56][57][58][59]. Roy et al [50] provided the first numerical results on the hydrodynamic and thermal fields of Al 2 O 3 /water nanofluid in a radial laminar flow cooling system, underlining a heat transfer enhancement up to 200% in the case of a nanofluid with 10% in nanoparticle volume concentration at a Reynolds number equal to 1200.…”
Section: Advances In Mechanical Engineeringmentioning
confidence: 98%
“…Furthermore, temperature-dependent thermophysical properties of nanofluids were found to have a marked bearing on the simulation results. Manca et al [57] numerically investigated the confining effects on impinging slot jets in the turbulent regime, such as for Reynolds numbers, ranging from 5000 to 20000. They adopted the single-phase approach in order to describe the Al 2 O 3 /water nanofluid behaviour for particle concentrations up to 5%.…”
Section: Advances In Mechanical Engineeringmentioning
confidence: 99%
“…Al 2 O 3 -water nanofluids are selected as working substances in this study [29,30], which are assumed as the mixtures of base fluid (water) and Al 2 O 3 nanoparticle with 30 nm diameter. The physical properties of the base fluid and Al 2 O 3 nanoparticle [31,32] are shown in Table 1, in which the reference temperature is 293 K. A single-phase model [33] is used to evaluate the physical properties of Al 2 O 3 -water nanofluids, and based on the assumptions that the aluminium oxide nanoparticle is spherical and homogeneously suspended in the base fluid, the following models are used to compute density, specific heat, dynamic viscosity, and thermal conductivity, respectively. Obtained from the above data and models, the physical properties of Al 2 O 3 -water nanofluids are shown in Table 2.…”
Section: Physical Properties Of Nanofluidsmentioning
confidence: 99%